EFFECT OF WORK STRES TO THE EMPLOYEE’S TURNOVER INTENTION - Dendi Sanjaya; Shalahuddin; Dodi Apriadi; Ferawati Usman; Rahmi Nur Islami (Jurnal Manajemen Dan Bisnis, 2023)
At the work, stress work is required in order to increase employee’s work. However, if a person chases the ambition and having an over pressure at work, it will cause distress to appear which causing an employee has a desire to search for a new job that has correspond with their ambition and workload. Comfortability, and inconvenience of an employee to their working environment will show desire to search for a new work. This research was arranged to explain the definition of work stress, turnover, what is turnover intention, and the correlation of turnover intention with work stress. The type of data used to create this research is qualitative data by amassing scientific researches which the source was from Google Scholar and Garda Rujukan Digital or GARUDA. This research showed that there was a positive impact between work stress with employee’s turnover intention.